Effects of positive airway pressure therapy on red blood cells in patients with obstructive sleep apnea - Coelho-Valentim, Cristina (2020)
Introduction: Obstructive Sleep Apnea (OSA) syndrome is characterized by recurrent arousals from sleep and intermittent hypoxemia. We recently demonstrated that OSA can cause alterations in the red blood cells (RBC) proteome that may be associated with OSA outcomes. Here we intend to investigate whether the positive airway pressure (PAP) treatment can revert/modulate these proteome alterations.